Peran etnomatematika dalam kehidupan sosial: Hubungan matematika dan budaya - Ulya, Diah Mariatul (Maliki Interdisciplinary Journal, 2024)
This article highlights the important role of ethnomathematics in social life, highlighting the complex relationship between mathematics and culture. Using a qualitative approach and library techniques to analyze primary and secondary data from various sources to examine the contribution of culture to the development of mathematical understanding. This study highlights that mathematics is not only an academic discipline, but is also an integral part of everyday life and is manifested in various cultural practices. Examples from Javanese, Papuan, and Sundanese cultures show how mathematical concepts are reflected in the arts, traditions, and way of life of society. The concept of ethnomathematics provides a deeper understanding of the intellectual heritage and local wisdom contained in each cultural tradition. The aim of this research is to awaken a love of culture and realize the importance of mathematics in social life.